(untitled) (Journal of the College of Basic Education, 2023)
The research aimed to reveal the formal features and contents of the drawings of female artists in Iraqi Kurdistan, for the period between (1994-2008), and the descriptive and analytical approach was followed as a research method. (22) paintings were deliberately selected as a sample for the research. They were analyzed according to a form consisting of (9) units: (shape as an element, form as composition, form as style, line, space, shape-space relationship, technique , content, the relationship of form to content) and the results showed that organic forms (human), rhythmic composition (axial and central), expressive style, curved lines, traditional drawing technique, and direct contents ranked first in the drawings of the artists in question, as was Put forward a number of recommendations and proposals.